Climate smart rice innovations to reduce the impact of climate change on the livelihood of value chain actors - Ndindeng, S.A.; Zenna, N.; Dossou-Yovo, Elliott Ronald; Arouna, A.; Yadav, S.; Semwal, V.; Ibrahim, A.; Futakuchi, K.; Manneh, B. (Africa Rice Center, 2023)
Introduction Rice is a major source of nutrients, largely contributing to the food and nutrition security for millions of people in Africa although most countries still rely on huge imports to meet local demand. Extreme temperatures, drought, flooding, and high salinity are climate change related stresses that negatively affect rice yield and grain quality. Thus, tackling these constraints is a critical action to increasing rice self sufficiency in Cameroon and Africa in general. Methods The Africa Rice Center in partnership with the National Agricultural Research and Extension Services of its 28 member States operating within the framework of the Africa-wide Taskforces has developed, tested, validated, and are deploying breeding, agronomic and post-harvest approaches to mitigate the negative impacts of climate change on rice yield and quality in Africa. Results Breeding approaches have led to the development of drought, cold, submergence, stagnation flood, salinity, and anaerobic germination tolerant varieties that are also resistant or tolerant to biotic stresses. These have demonstrated better yields and grain quality under stressed conditions compared to counterparts lacking those specific traits. The system of rice intensification and alternate wetting and drying, mid-season drainage, smart-valleys approach for inland development, solar-powered irrigation system, no-till and rice straw mulching are agronomic approaches developed and these approaches have demonstrated significant increase in yield and grain quality compared to alternative approached under climate change stress conditions. Post-harvest approaches have focused on reducing grain breakages, chalkiness, mycotoxin contamination, insecticide and fungicide use, deforestation and value addition to broken rice and rice milling byproducts using environmentally friendly methods. Post-harvest innovations here include using improved rice parboiling fueled by rice husk, solar-powered hermetic storage systems, processing of fine broken rice into flour for porridges and bakery products and use of rice husk fan-assisted stoves for household cooking and the cottage processing industry. Conclusions and recommendations Although climate change is a serious threat to rice production affecting both yield and quality, African governments will have to implement policy measures that enhance the scaling and adoption of climate smart rice innovation developed by AfricaRice to mitigate the impact of climate change if they aspire to reduce rice imports.